Plant balls from a Pomeranian lake, their invertebrate and microplastic components - Witalis Bartosz; Kornijów Ryszard (Oceanological and Hydrobiological Studies)
Two balls with similar diameters (approximately 11–12cm) were found on the bottom of Lake Białe (Kashubian Lake District) at depths of 4m and 7m. The structures were made of tightly-packed plant remains represented mainly by decaying leaves of Larix sp. The balls were colonised by invertebrates (Tubificinae, Hirudinea, Isopoda, and insect larvae). They also contained pollutants, namely microplastics in blue, white, red, and black colours with a length from 500 to 1000 μm. Four other balls had been earlier reported by another diver in the same lake. According to a report of the local press, similar balls have also been found in Lake Bobęcińskie (Bytowskie Lake District). This article aims to record the first appearance of larch balls in this area.